PENGUMPUL SAMPAH PERLU MENDAPATKAN PELAYANAN KESEHATAN KERJA : LITERATUR REVIEW - Mulyanasari, Fertin; Mulyono, Sigit (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
Waste pickers are a group of workers who are at risk of accidents and work-related diseases because they are exposed to sources of disease from rubbish piles. Various diseases and work accidents occur in waste pickers in various countries. To describe occupational health and safety problems that occur in waste pickers as well as efforts that can be made to improve occupational health and safety of waste pickers. Literature search through online databases on ScienceDirect, Wiley Online, and ProQuest with the keywords used